Farmers’ performance and subject pool effect in decentralized bargaining markets - Waichman, Israel; Ness, Christiane (Economics letters, 2012)
We report results from a decentralized bargaining market experiment conducted with farmers and students. Our results indicate that despite its bad reputation, performance is highly efficient (although not as efficient as the competitive equilibrium prediction). Farmers and students perform similarly regarding quantities, prices, and allocative efficiencies, but not regarding payoff allocations between buyers and sellers.